The mediating effect of teacher commitment in the relationship between burnout and role performance of early childhood teachers - Sungwon Kim; Jiyoung Lee (Frontiers in Education)
The purpose of this study is to examine the mediating effect of teacher commitment on the relationship between burnout and role performance of early childhood teachers. The sample consisted of 207 early childhood teachers in Seoul and Gyeonggi Province, selected through convenience sampling. Data collection was conducted over a period of 1 month in November 2020 with teachers who agreed to participate in the study. The results of this study were as follows: First, there was a negative correlation between early childhood teachers’ burnout and commitment, and between burnout and role performance. Furthermore, there was a positive correlation between teachers’ commitment and role performance. Second, early childhood teachers’ teacher commitment was found to partially mediate the relationship between burnout and role performance. This study is significant in that it is being published at a time when the integration of early childhood education and childcare is just beginning in South Korea, and it addresses the topic of teachers who will be most directly affected by the integration.